Viewpoint on the Application of Virtual Microscopy in Teaching at a Medical College in Saudi Arabia - Akhund, Shahid (Journal of Liaquat University of Medical & Health Sciences, 2023)
Conventional light microscopy (CLM) was the primary technique used to teach histology and pathology for a long time. However, it cannot view slides simultaneously, making it difficult for group discussions and cooperative learning. Multiple microscopes, glass slide production and storage, are expensive and require time-consuming maintenance. The invention of projectors and digital video cameras in the early 20th century made using CLM more effective. However, these tools could only be used by one person at a time, which prevented them from totally replacing CLM.1 the 1980s, the initial digital images were generated from histological slides, but it wasn't until the availability of personal computers with sufficient memory capacity that digital microscopy advanced rapidly, this led to the development of imaging converter programs and servers that facilitated the uploading of virtual slides to the internet, enabling image viewing and zooming capabilities. Presently, numerous systems can generate high-quality virtual images of histological tissues. Users can browse the images using a mouse or joystick, allowing them to navigate through different areas of the slide and simulate the zooming functionality of an optical microscope.